Hexa-band pattern reconfigurable antenna with defected ground plane. Issue 11 (2nd November 2021) - Singh, Ghanshyam; Kanaujia, Binod Kumar; Pandey, Vijay Kumar; Gangwar, Deepak; Kumar, Sachin
ABSTRACT: In this paper, a low-profile, compact hexa-band pattern reconfigurable antenna is presented. The proposed antenna consists of a square patch fed by a microstrip line of 50 Ω and a ground plane. The ground is loaded with a pair of the split-ring resonators and two rectangular slots that offer multiband operation and pattern reconfigurability. On the top surface of the antenna, two diodes (D1 and D2) are introduced to control current distribution and to achieve pattern diversity. The antenna operates at 2.4 GHz, 3.8 GHz, 4.35 GHz, 4.7 GHz, 5.5 GHz, and 6.25 GHz, with impedance bandwidth in the range of 1.01% to 4.09%. Depending upon the state of operation, the gain of the proposed reconfigurable antenna varies from 1.90 dBi to 2.82 dBi and pattern tilt of ±10 ° at 3.8 GHz, ±45 ° at 4.35 GHz, ±25 ° at 4.7 GHz, ±45 ° at 5.5 GHz, and ±45 ° at 6.25 GHz is observed. The prospective antenna is fabricated and practical inferences are compared with the simulated results. The experimental outcomes are found in good agreement with the simulated results, which validates the beam steering capability of the antenna.